Evaluation of Shape Array sensors to quantify the spatial distribution and seasonal rate of track settlement. (March 2021) - Yan, Ruobing; Take, W. Andy; Hoult, Neil A.; Meehan, Jonathan; Levesque, Christiane
Abstract: Rail track geometry irregularities can lead to ride discomfort for passengers and redistribution of wheel loads potentially causing derailments. Current techniques for monitoring track settlements involve the use of discrete sensors or vehicle mounted sensors, which make it difficult to capture either spatial or temporal variations in settlement. Shape Array sensors (SAA) can potentially be used to capture temporal variations in distributed track settlement profiles to monitor and investigate potential track geometry irregularities and inform track maintenance programs. In this study, a site with known ground deformation issues (i.e. soft spots) was monitored with both an SAA and intermittent LIDAR scans. The objectives of the research were to investigate the accuracy of the SAA for measuring track settlements based on a comparison with LIDAR data, use those measurements to assess track irregularities at the site, evaluate temporal and seasonal changes in rail deformation, and to gain insight into the underlying causes of the ground deformation issues. The SAA was found to provide comparable settlement measurements to those from the LIDAR with the added advantage that the data could be used to assess settlement rates. At this particular site, long-term rail settlements were found to be a function of seasonal/climatic conditions with slower settlement rates in the winter and higher rates in the summer. In addition, the measurements indicated that the deformation issues are potentially caused by an asymmetric bearing failure.